2006
DOI: 10.1093/aob/mcl041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Leaf Life Span, Photosynthesis and Defensive Traits Across Seven Species of Deciduous Broad-leaf Tree Seedlings

Abstract: These results indicate that species with a shorter leaf life span have higher photosynthetic productivity and are more susceptible to herbivore attack than species with a longer leaf life span. This supports the "cost-benefit hypothesis".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 26 publications
(31 reference statements)
1
41
1
1
Order By: Relevance
“…Across 41 rainforest trees, LLS was positively correlated to mass-based condensed tannin contents (Coley 1988). Across seven winter-deciduous trees in Japan, LLS was positively correlated to mass-based total phenolic contents, but it was not correlated to mass-based condensed tannin contents (Matsuki and Koike 2006). In the present study, LMA was positively correlated to N-based condensed tannins, but LLS was not correlated to either N-based condensed tannins or total phenolics (Table 3) nor to massbased condensed tannins or total phenolics (data not shown).…”
Section: Discussioncontrasting
confidence: 58%
“…Across 41 rainforest trees, LLS was positively correlated to mass-based condensed tannin contents (Coley 1988). Across seven winter-deciduous trees in Japan, LLS was positively correlated to mass-based total phenolic contents, but it was not correlated to mass-based condensed tannin contents (Matsuki and Koike 2006). In the present study, LMA was positively correlated to N-based condensed tannins, but LLS was not correlated to either N-based condensed tannins or total phenolics (Table 3) nor to massbased condensed tannins or total phenolics (data not shown).…”
Section: Discussioncontrasting
confidence: 58%
“…These differences in C/N may be more influenced by abiotic factors that shape plant ecophysiology ) than by a response to herbivory. Matsuki and Koike (2006) showed that across seven species of deciduous broad-leaved trees that differed in their leaf life span, C/N correlated negatively with total N and herbivore survival, revealing that older leaves with low nitrogen content were less suitable for caterpillar growth. Following monarch feeding on A. barjoniifolia and A. fascicularis, C/N increased; this could be a result of metabolite reallocation and changes in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These two coexisting species exhibited distinct leaf life spans, with P. koraiensis being 36-48 months and Q. mongolica being ca. 6 months (Matsuki and Koike, 2006). In this study, we expect to: (1) determine the appropriate light environment facilitating the highest survival and growth rates for the seedlings of both tree species; (2) compare the survival and growth of the two coexisting species under the same light level; (3) explain how NSC storage varied with natural light levels, and find their correlations with final survival for those two coexisting species.…”
Section: Introductionmentioning
confidence: 99%